Student Psychology in Early Childhood Education - Intima Uliz Zakiyah; Ellen Prima (Journal of Human Interaction and Social Studies, 2026)
Early childhood represents a critical developmental period during which fundamental psychological processes are established and shaped through interactions with educational and social environments. This study examined student psychology in early childhood education through a qualitative literature review that synthesized evidence from educational psychology, child development, and early childhood education research. Data were obtained from peer reviewed journal articles, scholarly books, and academic publications selected according to their theoretical and empirical relevance. The analysis employed qualitative content analysis involving literature identification, screening, coding, thematic synthesis, and interpretation. The findings indicate that psychological development is influenced by interconnected factors encompassing supportive developmental environments, meaningful learning experiences, and adaptive responses to changing educational contexts. Family and educational environments contribute to cognitive, emotional, and social development, while engaging learning approaches strengthen motivation, autonomy, creativity, and socioemotional competence. The review also highlights the growing importance of psychological adaptation in response to educational disruptions, digital learning environments, technological innovation, and emerging instructional challenges. These findings suggest that effective early childhood education requires an integrated psychological framework that supports holistic development, learning engagement, wellbeing, and educational resilience in contemporary learning environments.